THE INFOGRAPHIC-BASED INSTAGRAM LEARNING MEDIA DEVELOPMENT IN ESSAY WRITING STUDY ENGLISH EDUCATION - Ulfa Mujahidah; M. Fahri Yasin (Lingua, 2022)
Instagram Learning Media Development Based on Infographic on Essay Writing Subject at English Major The ADDIE method was used in this development research (Analyze, Design, Development, Implementation, and Evaluation). This study was carried out to determine the viability of learning media on Instagram. The steps in this research are analysis, design, development, implementation, and evaluation to measure feasibility, with validation the of test instrument, validation test material expert, validation test material expand validation test media expert students' responses as research subjects used questionnaires. The data was analyzed using the qualitative descriptive technique. This learning media is feasible to use, according to media experts, with a score of 78%. This learning medium is 100% feasible to use, according to the material expert. Based on the research subject's responses, this learning media is usable with an 80% score. The questions were 94% appropriate for the experts, according to the instrument validator. Based on these results, it is possible to conclude that learning media Instagram based on infographics is usable. Keywords: Instgaram, Infographic, Writing, ADDIE method.